Haiti : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Haiti's Request for Disbursement Under the Rapid Credit Facility. Coronavirus disease 2019 (COVID-19) poses a major challenge for Haiti, a country in a fragile situation with very limited healthcare services, just emerging from two years of socio-political instability and worsening economic hardship. Measures are being taken by the government to stop the spread of the virus and to cushion the economic impact of the shock. IMF emergency support under the Rapid Credit Facility will help fill the balance of payments gap and create fiscal space for essential health expenditures, income support to workers, and cash and in-kind transfers to households. In order to address the crisis, scarce budgetary resources will need to be allocated to critical spending on disease containment and increased social assistance to the most vulnerable. In order to ensure the appropriate use of emergency financing, the authorities should prepare monthly budget execution reports on COVID-19 expenditures and undertake an ex-post financial and operational audit of COVID-related operations.